Interpersonal Pragmatics and Critical Linguistics: A Critical Pragmatic Analysis - Dina Mardiana; Fathur Rokhman; Rustono Rustono; Hari Bakti M (International Conference on Science, Education, and Technology, 2021)
Pragmatics studies about the forms of language to understand the speaker's utterance meanings which bases its analysis on contexts. Interpersonal pragmatics is a rhetoric that has an explanatory value about the meaning and the power of communication. Interpersonal pragmatics includes interpersonal rhetoric as a strategy and conversational rule that must be obeyed in speaking activities to achieve the goals of the discourse cooperatively and politely. The speech where interpersonal rhetoric used contains ideological values ​​which are not sufficiently analyzed only by pragmatic studies, but also it can be analyzed by critical linguistics using critical discourse analysis (CDA). From the empirical and theoretical point of view, both can be partially applied as a complementary and generalizable approach in the critical pragmatics to conduct a study of interpersonal rhetoric and the ideological meaning of speech.